Synthetic approaches to the 2015–2018 new agrochemicals. (1st June 2021) - Jeanmart, Stephane; Edmunds, Andrew J.F.; Lamberth, Clemens; Pouliot, Martin; Morris, James A.
Graphical abstract: Abstract: In this review, the synthesis of 33 agrochemicals that received an international standardization organization (ISO) name between January 2015 and December 2018 is described. The aim is to showcase the broad range and scope of reactions, reagents and intermediates used to discover and produce the latest active ingredients addressing the crop protection industry's needs.